Bilingual Advantages in Inhibition or Selective Attention: More Challenges - Paap, Kenneth R.; Anders-Jefferson, Regina; Mason, Lauren; Alvarado, Katerinne; Zimiga, Brandon (Frontiers in Psychology, 2018)
A large sample (N=141) of college students participated in both a conjunctive visual search task and an ambiguous figures task that have been used as tests of selective attention. Tests for effects of bilingualism on selective attention were conducted by both partitioning the participants into bilinguals and monolinguals and by treating bilingualism as a continuous variable, but there were no effects of bilingualism in any of the tests. Bayes factor analyses confirmed that the evidence substantially favored the null hypothesis. These new findings mesh with failures to replicate language-group differences in congruency-sequence effects, inhibition-of-return, switch costs, and working memory capacity. The evidence that bilinguals are better than monolinguals at attentional control is equivocal at best.